2022
DOI: 10.1063/5.0076545
|View full text |Cite
|
Sign up to set email alerts
|

Violation of Hund’s rule in molecules: Predicting the excited-state energy inversion by TD-DFT with double-hybrid methods

Abstract: The energy difference (∆E ST ) between the lowest singlet (S 1 ) and triplet (T 1 ) excited state of a set of azaphenalene compounds, which is theoretically and experimentally known to violate Hund's rule giving rise to the inversion of the order of those states, is calculated here with a family of double-hybrid density functionals. That excited-state inversion is known to be very challenging to reproduce for TD-DFT employing common functionals, e.g. hybrid or range-separated expressions, but not for wavefunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 105 publications
(107 reference statements)
1
54
0
Order By: Relevance
“…Therefore, a reliable and cost-effective method for prediction for MR-TADF compounds is desirable, for example, the double-hybrid functionals, as revealed in the recent benchmark study on Hund's-rule-violating molecules. [45] Most compounds obey Hund's multiplicity rule, where their T 1 states lie below their S 1 states. Up to now, only few compounds violate Hund's rule, [46] showing a negative ΔE ST .…”
Section: Design Of Thermally-activated Delayed Fluorescence Emittersmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, a reliable and cost-effective method for prediction for MR-TADF compounds is desirable, for example, the double-hybrid functionals, as revealed in the recent benchmark study on Hund's-rule-violating molecules. [45] Most compounds obey Hund's multiplicity rule, where their T 1 states lie below their S 1 states. Up to now, only few compounds violate Hund's rule, [46] showing a negative ΔE ST .…”
Section: Design Of Thermally-activated Delayed Fluorescence Emittersmentioning
confidence: 99%
“…[46] Fortunately, a recent benchmark study by Sancho-Garcia et al showed that TD-DFT with double-hybrid functionals can give the correct negative feature of ΔE ST . [45] These methods can thus be used in computational high-throughput screening to further increase the number of Hund's-rule-violating molecules. The electron is more stable in the phase with lower electron affinity (larger negative energy values) and the hole is more stable in the material with the higher ionization energy.…”
Section: Design Of Thermally-activated Delayed Fluorescence Emittersmentioning
confidence: 99%
See 2 more Smart Citations
“…Shortly speaking, although this method is able to provide negative values for ∆E ST , the results appear to be affected by a systematic error. The use of double-hybrid functionals has been recently and more systematically examined [52], with some of the models assessed being promising enough to display accurate individual excitation energies: we thus refer the reader to that study for further information and confirmation about the key role played by double excitations into the final values.…”
Section: Td-dft Calculationsmentioning
confidence: 99%